A method for preparing a negative electrode of a biomass sodium ion battery

By preparing biomass into hard carbon materials with wrinkled structures, the shortcomings of sodium ion battery anode materials in sodium storage performance, rate performance and cycle life are solved, and efficient sodium ion diffusion and electrochemical performance are achieved.

CN115101723BActive Publication Date: 2025-03-18CENT SOUTH UNIV
View PDF 2 Cites 0 Cited by

Patent Information

Application Number
CN202210808277.1
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2022-07-11
Publication Date
2025-03-18
Estimated Expiration
2042-07-11

AI Technical Summary

Technical Problem

The existing sodium ion battery anode materials have shortcomings in sodium storage performance, rate performance and cycle life, especially since sodium ions are difficult to effectively embed in traditional anode materials.

Method used

Biomass is used as raw material to achieve a unique fold structure by rapid cooling after carbonization, thereby increasing the layer spacing and defect number, promoting electron-to-movement mechanics and sodium ion diffusion.

Benefits of technology

While ensuring high conductivity, the sodium ion diffusion rate and electrochemical performance are improved, and the sodium storage capacity and cycle stability of the negative electrode material are enhanced.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN115101723B_ABST
    Figure CN115101723B_ABST
Patent Text Reader

Abstract

The present invention provides a method for preparing a negative electrode of a biomass sodium ion battery, comprising the following steps: step S1, washing the natural biomass raw material with deionized water and alcohol through an ultrasonic cleaning machine to remove surface dust and pollutants soluble in water and alcohol, and placing it in a blast drying oven for drying after washing; step S2, soaking the material obtained in step S1 in an acid solution, then washing it with deionized water to neutrality, and drying it in a vacuum drying oven; step S3, mixing the material obtained in step S2 with a crystal template and placing it in an ark, calcining it in a tube furnace for carbonization process: under an inert atmosphere, the heating rate is 1 to 5°C / min, the carbonization temperature is 800°C to 1600°C, the insulation time is 1 to 5h, and it is quickly cooled to room temperature after the insulation time is reached to obtain the final hard carbon material. The method for preparing a negative electrode of a biomass sodium ion battery provided by the present invention can promote electron transfer kinetics, increase the sodium ion diffusion rate, and achieve the improvement of electrochemical performance.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to the technical field of sodium ion batteries, and in particular to a method for preparing a biomass sodium ion battery negative electrode. Background Art

[0002] Lithium-ion batteries are widely used in research due to their high energy density and excellent cycle stability. However, the lack of lithium resources, uneven global distribution, and high manufacturing costs have limited their further development. Sodium-ion batteries have similar energy storage mechanisms to lithium-ion batteries, and their negative electrode materials have certain commonalities. In addition, sodium is highly abundant and inexpensive, so sodium-ion batteries are expected to replace lithium-ion batteries and become one of the new generation of energy storage systems with excellent performance. However, the radius of sodium ions is Lithium ion radius The large size makes it difficult for sodium ions to be embedded in the negative electrode materials of traditional lithium-ion batteries. The development of negative electrode materials with high sodium storage performance, high rate performance and excellent cycle life is the key to the application of sodium-ion batteries. Therefore, it is crucial to improve the driving force of the negative electrode material's electrical / ion transfer and increase the number of active sites for sodium storage.

[0003] Carbon-based materials are considered one of the most promising negative electrode materials due to their considerable ion storage capacity, good conductivity and excellent thermal / chemical stability. Soft carbon and hard carbon are the two most common amorphous carbon-based materials on the market. Among them, hard carbon materials are considered to be more ideal negative electrode materials for sodium ion batteries due to their low cost, non-toxicity, environmental protection, and low sodium storage potential. The sources of hard carbon material precursors are mainly divided into biomass-based, polymer-based, and coal-based carbon materials. Biomass materials stand out among many materials due to their abundance, low cost, sustainability and economic advantages, and are the first choice for commercial negative electrode materials. However, poor rate performance and low reversible capacity are still a major challenge for its commercial application. Hard carbon, also known as amorphous carbon, is mainly composed of disordered structures, and also has some randomly oriented graphite-like microcrystalline regions. The existing biomass carbon conversion process focuses on changing the structure of the prepared hard carbon by changing the pyrolysis temperature. Studies have shown that the increase in pyrolysis temperature is usually accompanied by an increase in graphitization, an increase in conductivity, a decrease in defects, and a decrease in irreversible capacity loss, but it inevitably causes a decrease in interlayer spacing, which in turn leads to a decrease in sodium ion transport capacity and sluggish kinetics, ultimately causing the negative electrode material to exhibit a lower reversible sodium storage capacity and poor cycle performance. Therefore, the above problems cannot be solved by simply changing the pyrolysis temperature.

[0004] In view of this, it is necessary to provide a new process to solve the above technical problems. Summary of the invention

[0005] The technical problem to be solved by the present invention is to provide a method for preparing a biomass sodium ion battery negative electrode, using abundant and low-cost biomass as raw material, and realizing a unique wrinkled structure by rapid cooling after carbonization, while ensuring high conductivity characteristics, increasing the interlayer spacing and defects, thereby promoting electron transfer kinetics, increasing the sodium ion diffusion rate, and achieving improved electrochemical performance.

[0006] In order to solve the above problems, the technical solution of the present invention is as follows:

[0007] A method for preparing a biomass sodium ion battery negative electrode comprises the following steps:

[0008] Step S1, washing the natural biomass raw material with deionized water and alcohol through an ultrasonic cleaning machine to remove surface dust and pollutants soluble in water and alcohol, and then drying it in a blast drying oven;

[0009] Step S2, soaking the material obtained in step S1 in an acid solution, then washing with deionized water until neutral, and drying in a vacuum drying oven;

[0010] Step S3, mixing the material obtained in step S2 with the crystal template and placing them in an ark, calcining them in a tube furnace for carbonization, the carbonization process is: under an inert atmosphere, the heating rate is 1 to 5°C / min, the carbonization temperature is 800°C to 1600°C, and the holding time is 1 to 5h; after the holding time is reached, the mixture is quickly cooled to room temperature to obtain the final hard carbon material;

[0011] Among them, the rapid cooling method is water quenching or liquid nitrogen cooling. After rapid cooling, the biomass-derived hard carbon material has a unique wrinkled structure and a larger interlayer spacing, and the porosity and number of defects of the material increase.

[0012] Furthermore, in step S1, the natural biomass raw material includes at least one of plant petals, rhizomes, fruits, and animal hair.

[0013] Furthermore, in step S2, the acid solution includes one or more of hydrochloric acid, nitric acid, and sulfuric acid, the acid concentration is 0.1M to 3M, and the soaking time is 5 to 12 hours.

[0014] Furthermore, in step S3, the crystal template is at least one of graphite, graphene, and graphene oxide.

[0015] Furthermore, in step S3, the material obtained in step S2 and the crystal template are mixed by ball milling or ultrasonic mixing.

[0016] Furthermore, the inert atmosphere is argon or nitrogen.

[0017] Compared with the prior art, the method for preparing a biomass sodium ion battery negative electrode provided by the present invention has the following beneficial effects:

[0018] The method for preparing the negative electrode of a biomass sodium ion battery provided by the present invention adopts biomass materials to prepare hard carbon materials as the negative electrode of the sodium ion battery. From the perspective of green and recyclability, the strategy of synthesizing electrode materials using biomass is of great significance, and the carbon derived from biomass exhibits good electrochemical performance, which is attributed to the fact that carbon inherits the unique natural morphology, structure and properties of biomass to a certain extent. The higher the carbonization temperature, the higher the degree of graphitization of the hard carbon material, the increased conductivity, and the reduced interlayer spacing and number of defects. However, after carbonization, rapid cooling can be performed to obtain a carbon material with a wrinkled structure. While ensuring high conductivity, the interlayer spacing and number of defects increase, which is conducive to effective sodium diffusion and embedding, and the sodium ion interaction rate is increased. The wrinkled structure can increase the contact area of ​​the electrolyte, which is conducive to the embedding of sodium ions, and the defects can provide more active sites, thereby effectively promoting ion diffusion and charge transfer.

[0019] The method for preparing the biomass sodium ion battery negative electrode of the present invention increases the interlayer spacing while ensuring high conductivity through rapid cooling, and the extremely wide interlayer spacing allows rapid electrolyte penetration, improved ion transfer kinetics, and easier embedding of sodium ions; in addition, the carbon material derived from the biomass itself also has a porous structure, which is beneficial to the effective penetration of the electrolyte during the cycle, thereby promoting electron transfer kinetics and increasing the sodium ion diffusion rate, thereby synergistically improving the electrochemical performance in many aspects. BRIEF DESCRIPTION OF THE DRAWINGS

[0020] In order to more clearly illustrate the technical solutions in the embodiments of the present invention, the following briefly introduces the drawings required for use in the description of the embodiments. Obviously, the drawings described below are only some embodiments of the present invention. For ordinary technicians in this field, other drawings can be obtained based on these drawings without creative work.

[0021] Figure 1 is a SEM image of the hard carbon material obtained in Example 1;

[0022] Figure 2 The hard carbon material obtained in Example 1 is used as the negative electrode material of sodium ion battery at 50 mA·g -1 Cyclic performance curve under current density of ;

[0023] Figure 3 It is the GITT test curve diagram of the hard carbon material obtained in Example 1 as the negative electrode material of the sodium ion battery and the corresponding sodium ion diffusion coefficient during the charge and discharge process. DETAILED DESCRIPTION

[0024] In order to enable those skilled in the art to better understand the technical solutions in the embodiments of the present invention and to make the above-mentioned objects, features and advantages of the present invention more obvious and understandable, the specific implementation modes of the present invention are further described below.

[0025] The endpoints and any values ​​of the ranges disclosed in this article are not limited to the precise ranges or values, and these ranges or values ​​should be understood to include values ​​close to these ranges or values. For numerical ranges, the endpoint values ​​of each range, the endpoint values ​​of each range and the individual point values, and the individual point values ​​can be combined with each other to obtain one or more new numerical ranges, which should be considered as specifically disclosed in this article.

[0026] A method for preparing a biomass sodium ion battery negative electrode comprises the following steps:

[0027] Step S1, washing the natural biomass raw material with deionized water and alcohol through an ultrasonic cleaning machine to remove surface dust and pollutants soluble in water and alcohol, and then drying it in a blast drying oven;

[0028] Wherein, the natural biomass raw material includes at least one of plant petals, rhizomes, fruits, and animal hair;

[0029] Step S2, soaking the material obtained in step S1 in an acid solution, then washing with deionized water several times until neutral, and drying in a vacuum drying oven;

[0030] The acid solution includes one or more of hydrochloric acid, nitric acid and sulfuric acid, the acid concentration is 0.1M to 3M, and the soaking time is 5 to 12 hours;

[0031] Acid immersion can remove some pollutants, and during the immersion process, the acid can effectively penetrate the graphite structure of the exfoliated sample, so that the interlayer spacing increases, which is conducive to the insertion / extraction of sodium ions. Specifically, the acid concentration can be 0.1M, 0.5M, 0.8M, 1.0M, 1.5M, 2.0M, 2.5M or 3M, or other concentration values ​​within this range; the immersion time is 5h, 6h, 7h, 8h, 9h, 10h, 11h or 12h, or other values ​​within this range;

[0032] Step S3, mixing the material obtained in step S2 with the crystal template and placing them in an ark, calcining them in a tube furnace for carbonization, the carbonization process is: under an inert atmosphere, the heating rate is 1 to 5°C / min, the carbonization temperature is 800°C to 1600°C, and the holding time is 1 to 5h; after the holding time is reached, the mixture is quickly cooled to room temperature to obtain the final hard carbon material;

[0033] Among them, the rapid cooling method is water quenching or liquid nitrogen cooling. After rapid cooling, the biomass-derived hard carbon material has a unique wrinkled structure and a larger interlayer spacing, and the porosity and number of defects of the material increase, which is conducive to accommodating more sodium ions and has a higher reversible sodium storage capacity;

[0034] In this embodiment, the crystal template is at least one of graphite, graphene, and graphene oxide. The introduction of the crystal template can improve the degree of ordering of the hard carbon material; and the material and the crystal template are mixed by ball milling or ultrasonic mixing;

[0035] In this embodiment, the inert atmosphere is argon or nitrogen;

[0036] In this embodiment, the carbonization temperature can be 800°C, 900°C, 1000°C, 1100°C, 1200°C, 1300°C, 1400°C, 1500°C or 1600°C, or other temperature values ​​within this range; the heating rate can be 1°C / min, 2°C / min, 3°C / min, 4°C / min or 5°C / min, or other values ​​within this range; the holding time can be 1h, 2h, 3h or 4h, or other values ​​within this range.

[0037] The following is a detailed description of the method for preparing the biomass sodium ion battery negative electrode of the present invention through specific examples.

[0038] Example 1

[0039] A method for preparing a biomass sodium ion battery negative electrode comprises the following steps:

[0040] Step S1, washing the osmanthus leaves with deionized water and alcohol in an ultrasonic cleaning machine to remove surface dust and pollutants soluble in water and alcohol, and then drying them in a blast drying oven;

[0041] Step S2, soaking the material obtained in step S1 in a 1M hydrochloric acid solution for 6 hours, then washing with deionized water several times until neutral, and drying in a vacuum drying oven at a drying temperature of 80° C. for a drying time of 24 hours;

[0042] Step S3, dispersing the material obtained in step S2 and graphene oxide in an ethanol solution, centrifugally drying and placing them in an ark, and calcining them in a tubular furnace for carbonization: under an argon atmosphere, the heating rate is 5°C / min, the carbonization temperature is 1000°C, the insulation time is 1 to 5 hours, and after the insulation time is reached, it is quickly cooled to room temperature to obtain the final hard carbon material.

[0043] See also Figure 1 , is the SEM image of the hard carbon material obtained in Example 1, Figure 1(a) It can be seen that the hard carbon material prepared in Example 1 has a porous structure. Figure 1 (b) It can be seen that the hard carbon material prepared by the present invention has a wrinkled structure and an increased number of defects, which will provide sufficient active sites to absorb sodium ions, thereby promoting the increase in the diffusion rate of sodium ions to improve the electrochemical performance.

[0044] The hard carbon material, acetylene black and PVP prepared in Example 1 were mixed and ground in a ratio of 8:1:1, and NMP was dripped into the mixture after grinding and stirred thoroughly (24 hours) to complete the slurry preparation. The slurry was coated on the copper foil surface, and after drying, the electrode was punched to prepare the electrode, and the sodium sheet was used as the counter electrode to assemble the button battery.

[0045] See also Figure 2 , is the hard carbon material obtained in Example 1 as the negative electrode material for sodium ion batteries at 50 mA·g -1 Cyclic performance curve at current density of Figure 2 It can be seen that after 100 cycles, the specific capacity of the carbon material obtained by rapid cooling is 298.3 mAh g -1 , while the capacity of the carbon material obtained by natural cooling after 100 cycles was only 194.2 mAh g -1 .

[0046] See also Figure 3 , is the GITT test curve of the hard carbon material obtained in Example 1 as the negative electrode material of the sodium ion battery and the corresponding sodium ion diffusion coefficient during the charge and discharge process. Figure 3 It can be seen that the diffusion coefficient of the hard carbon material obtained by rapid cooling is higher than that of the hard carbon material obtained by natural cooling. This result well reflects that rapid cooling enables the hard carbon material to have a higher ion diffusion driving force, and thus its sodium storage performance is better than that of the hard carbon material obtained by natural cooling.

[0047] Compared with the prior art, the method for preparing a biomass sodium ion battery negative electrode provided by the present invention has the following beneficial effects:

[0048] The method for preparing the negative electrode of a biomass sodium ion battery provided by the present invention adopts biomass materials to prepare hard carbon materials as the negative electrode of the sodium ion battery. From the perspective of green and recyclability, the strategy of synthesizing electrode materials using biomass is of great significance, and the carbon derived from biomass exhibits good electrochemical performance, which is attributed to the fact that carbon inherits the unique natural morphology, structure and properties of biomass to a certain extent. The higher the carbonization temperature, the higher the degree of graphitization of the hard carbon material, the increased conductivity, and the reduced interlayer spacing and number of defects. However, after carbonization, rapid cooling can be performed to obtain a carbon material with a wrinkled structure. While ensuring high conductivity, the interlayer spacing and number of defects increase, which is conducive to effective sodium diffusion and embedding, and the sodium ion interaction rate is increased. The wrinkled structure can increase the contact area of ​​the electrolyte, which is conducive to the embedding of sodium ions, and the defects can provide more active sites, thereby effectively promoting ion diffusion and charge transfer.

[0049] The method for preparing the biomass sodium ion battery negative electrode of the present invention increases the interlayer spacing while ensuring high conductivity through rapid cooling, and the extremely wide interlayer spacing allows rapid electrolyte penetration, improved ion transfer kinetics, and easier embedding of sodium ions; in addition, the carbon material derived from the biomass itself also has a porous structure, which is beneficial to the effective penetration of the electrolyte during the cycle, thereby promoting electron transfer kinetics and increasing the sodium ion diffusion rate, thereby synergistically improving the electrochemical performance in many aspects.

[0050] The embodiments of the present invention are described in detail above, but the present invention is not limited to the described embodiments. For those skilled in the art, various changes, modifications, substitutions and variations made to these embodiments without departing from the principles and spirit of the present invention are still within the protection scope of the present invention.

Claims

1. A method for preparing a biomass sodium ion battery negative electrode, characterized in that: The steps include: Step S1, washing the natural biomass raw material with deionized water and alcohol through an ultrasonic cleaning machine to remove surface dust and pollutants soluble in water and alcohol, and then drying it in a blast drying oven; the natural biomass raw material includes at least one of plant petals, rhizomes, fruits, and animal hair; Step S2, soaking the material obtained in step S1 in an acid solution, then washing with deionized water until neutral, and drying in a vacuum drying oven; the acid solution includes one or more of hydrochloric acid, nitric acid, and sulfuric acid, the acid concentration is 0.1 M to 3 M, and the soaking time is 5 to 12 h; Step S3, mixing the material obtained in step S2 with the crystal template and placing them in an ark, calcining them in a tube furnace for carbonization, the carbonization process is: under an inert atmosphere, the heating rate is 1-5°C / min, the carbonization temperature is 800°C-1600°C, and the holding time is 1-5 h; after the holding time is reached, the mixture is quickly cooled to room temperature to obtain the final hard carbon material; the crystal template is at least one of graphite, graphene, and graphene oxide; Among them, the rapid cooling method is water quenching or liquid nitrogen cooling. After rapid cooling, the biomass-derived hard carbon material has a wrinkled structure, the interlayer spacing increases, and the porosity and number of defects of the material increase.

2. The method for preparing a biomass sodium ion battery negative electrode according to claim 1, characterized in that: In step S3, the material obtained in step S2 and the crystal template are mixed by ball milling or ultrasonic mixing.

3. The method for preparing a biomass sodium ion battery negative electrode according to claim 1, characterized in that: The inert atmosphere is argon or nitrogen.

Citation Information

Patent Citations

  • Carbon biomass shell-based hard carbon / graphite composite material and preparation method therefor

    CN107068997A

  • Carbon material

    JP2016056038A